Sex determination from dry mandibles using metric methods: Sex Determination, Dry mandibula (Bulletin of the International Association for Paleodontology, 2024)
Objectives: The article discusses sex determination as the basis for paleodemographic studies to describe ancient societies, metric methods using mandibles.Material and Methods: Two commonly used methods in anthropology for sex determination are the anthroposcopic method and the anthropometric method. The anthroposcopic method involves a macroscopic examination of skeletal materials to identify distinguishing criteria between sexes. The article notes that sex can be determined with 100% accuracy from the pelvis and 90% accuracy from the skull, provided the skeletal remains are intact. In contrast, the anthropometric method relies on statistical analysis of results obtained from metric measurements of skeletons to reveal sex differences. This method is considered more objective because it relies on numerical data, providing precise differences between sexes. Many researchers have used metric measurements to confirm morphological differences between male and female individuals, as mentioned in the article. In this study, 11 different measurements were taken on the mandible (jawbone) and statistically evaluated, resulting in a significant difference between sexes, which allows for sex determination with an accuracy of 80% or higher.Results: Consequently, the article highlights the importance of sex determination in palaeodemographic studies and emphasizes the utility of both anthroposcopic and anthropometric methods. It underscores the significance of the mandible as a reliable skeletal material, even when other bones are absent or fragmented, and emphasizes the precision of sex determination through metric measurements.